Problems of Teaching Practical Biology in Senior Secondary Schools - Ahmad Abdussemiu (Universitas Pendidikan Indonesia (UPI), 2022)
Biology is taught and learned in Nigerian schools from nursery to secondary school and postsecondary institutions. Biology science education attempts to study and comprehend the live organism and how it functions, students must have first-hand experience with and observation of the relevant events. The purpose of this research is to look into the challenges of teaching practical biology in senior secondary school. The research was conducted using a descriptive research approach. Education district IV in Lagos State was chosen using a random selection process. Seventy-one Biology instructors were chosen at random from among the forty schools to take part in the study. The data for the study was collected using the Problems of Teaching Practical Biology Questionnaire (PTPBQ). The findings identified a number of difficulties, including a paucity of specimens for Biology practicals and insufficient or unsatisfactory equipment for Biology practicals. It was observed that improvising the specimen by the teacher, students, and principals, as well as aid from the Parent-Teacher Association and Non-Governmental Organizations in the acquisition of realistic materials and equipment, are viable solutions to these problems.